BS EN 17020-4. Extended application of test results on durability of self-closing for doorsets and openable windows. Part 4. Durability of self-closing of fire resistance hinged and pivoted metal framed glazed doorsets and openable windows (24th February 2020) - British Standards Institution,
No abstract available